Estabilidade para um problema de transmissão viscoelástica - Lobeiro, Adilandri Mércio (2003)
We consider a transmission problem of viscoelastic waves. That is, we study the wave propagations over materials consisting of elastic and viscoelastic components in a bounded, open connected set with smooth boundary and transmission boundary conditions. We show that for this type decay of the solution, no matter how small is its size.